2012
DOI: 10.1007/s00432-012-1342-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of focal adhesion kinase correlates with increased lymph node metastasis and poor prognosis in non-small-cell lung cancer

Abstract: FAK overexpression is a promising pathological factor to predict aggressive behavior and prognosis in patients with NSCLC, particularly in the adenocarcinoma subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…In addition, FAK plays a critical role in TGF-b1-induced EMT. Its overexpression was significantly associated with positive lymph node metastasis and worse overall survival of patients with lung adenocarcinoma (25). Because ACTA2 not only mediates alterations in the mechanical properties of cancer cells, but also regulates the expression of signaling proteins that significantly influence the clinical outcome of lung adenocarcinoma, this protein could be used as a therapeutic target for lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FAK plays a critical role in TGF-b1-induced EMT. Its overexpression was significantly associated with positive lymph node metastasis and worse overall survival of patients with lung adenocarcinoma (25). Because ACTA2 not only mediates alterations in the mechanical properties of cancer cells, but also regulates the expression of signaling proteins that significantly influence the clinical outcome of lung adenocarcinoma, this protein could be used as a therapeutic target for lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another study demonstrated correlation between FAK overexpression and more advanced stages of disease using 153 NSCLC frozen tissues in Chinese patients. 10 The authors reported that FAK overexpression was associated with lymph node metastasis and more advanced stages of NSCLC. FAK overexpression was independently associated with worse overall survival, suggesting it as a significant prognostic factor in addition to pathologic stage.…”
Section: Discussionmentioning
confidence: 99%
“…79 FAK has been shown to be overexpressed in colon tumors compared to normal matched samples by both immunohistochemistry and RT-PCR. 6 Recently, FAK was found to be overexpressed in lung tumors, and its higher expression correlated with nodal spread and advanced disease stages, 1012 suggesting its important role in lung cancer progression and metastasis. Moreover, activation of FAK, along with SRC, promote cell migration and adhesion in LKB1-deficient KRAS mutant lung tumors, a genotype associated with high propensity for nodal and distant metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Results from our clinical cohort suggest that ovarian cancer is similar to other solid tumours, including breast and lung, in which increased transcript copy numbers of FAK and paxillin are linked to poor prognosis [23][24][25][26][27][28]. Our clinical cohort isolated those groups of patients who had poorly differentiated tumours, and those patients who died from the disease and/or had associated incidence.…”
Section: Discussionmentioning
confidence: 98%